IS-USG: INTELLIGENCE SYSTEM ULTRASONOGRAPHY Machine Learning Implementation for Recognition of Pregnant Sheep in Gumukmas Multifarm Jember - Denny Trias Utomo; Hariadi Subagja; Nilla Putri Rosidania; Adhe Wahyu Trilaksana; Mohammad Rizal Maulana Najib; Septiananda Rifqi Nurhidayat; Ammar Akhtar Addany (Engineering And Technology Journal, 2024)
In 2023, the government’s program related to food independence emphasizes the importance of meat independence, including goat meat. CV. Gumukmas Multi Farm Jember faces several challenges in managing pregnant sheep, such as early detection of pregnancy, preventing abortion, and managing sheep health history. Therefore, the Intelligence System Ultrasonography (IS-USG) system was developed to detect sheep pregnancy more accurately and integrate medical data with the help of machine learning. This system allows automatic monitoring of pregnancy conditions and fetal health, and recommends interventions such as probiotic feeding. IS-USG is implemented using a web and mobile-based client-server architecture, with Laravel and MySQL backends, and RESTful API integration for real-time data synchronization. Testing was conducted to evaluate the effectiveness of the system, and initial results showed that this system can improve sheep reproductive management, accelerate pregnancy detection, and minimize the risk of birth failure.